Template synthesis and characterization of carbon nanomaterials from ferrocene crystals - Cherkasov, Nikolay; Savilov, Serguei V.; Ivanov, Anton S.; Egorov, Alex V.; Lunin, Valery V.; Ibhadon, Alex O. (Applied Surface Science, 2014)
Filamentous ribbon-like structures of highly disordered carbon of thickness 10-100 nm built from merged individual carbon nanofibers were synthesised by chemical vapour deposition from saturated ferrocene-benzene solution at 950 K. The materials obtained were characterized by electron microscopy, x-ray and electron diffraction, Raman spectroscopy and a possible growth mechanism for their formation was proposed and discussed. The synthesis demonstrates the possibility of a template growth of carbon nanomaterials and supports the vapour-solid-solid growth model of carbon materials because the catalysing metal particles are solid under the experimental conditions. Due to the large number of structural defects, filamentous structure, submicrometer thickness and low intraparticle diffusion of the nanomaterials, they can find application in catalysis as catalyst supports and sorbents. © 2014 Elsevier B.V.
Keywords: Ribbons; Nanomaterials; Chemical vapor deposition; Carbon nanotubes; Ferrocene